Analysis of Students' Critical Reasoning Ability in Islamic Banking Accounting Learning at Muhammadiyah Sampit Vocational School - Sukarini Mutiara Putri; Siti Halimah; Ifan Julianta (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Critical reasoning ability is one of the essential skills that students must possess to meet the demands of education in the 21st century. This study aims to describe and analyze students' critical reasoning skills in the Islamic Banking Accounting subject at SMK Muhammadiyah Sampit. The method used in this study is qualitative with a descriptive approach. The subjects of this study consisted of three 11th-grade students majoring in Islamic Banking Accounting who were selected through a purposive sampling technique based on high, medium, and low levels of critical reasoning ability. Data collection in this study was carried out through semi-structured tests and interviews, then analyzed using the model from Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. Data analysis was supported by NVivo software with Word Cloud and Word Tree visualizations. The research findings indicate that students' critical reasoning ability is reflected in three indicators: acquisition and processing of information and ideas, analysis and evaluation of reasoning, and reflection of thinking in decision-making. Students with high levels of critical reasoning ability show superior abilities in understanding information, analyzing problems, and reflecting on the learning process when compared to those with medium and low levels of ability. The results of this study reveal that the skills of understanding information, analyzing problems, and reflecting on learning experiences are interrelated in forming students' critical reasoning abilities in learning Islamic Banking Accounting.